Climate Projections Using Lars-Wg For Estimating Irrigation Water Requirements For Rice Crops With Hargreaves Method - Ferdi Aleyogi Pranata (Fakultas Pertanian, 2025)
Climate change is a significant challenge for the agricultural sector in Indonesia, particularly in rice cultivation, which is affected by temperature fluctuations, rainfall patterns, and extreme weather events. It has significantly impacted rice productivity, thus requiring mitigation strategies through climate projections to estimate irrigation water needs. This study employs the HadGEM model under three carbon dioxide (CO2) emission scenarios low, medium, and high using LARS-WG to project future climate conditions over the next 20 years in West Sumatra and West Kalimantan. The projected variables include minimum temperature, maximum temperature, precipitation, and solar radiation duration. These projections form the basis for estimating irrigation water requirements for rice crops in both regions under various climate scenarios. Observed and projected data were tested using the Kolmogorov-Smirnov (KS) test, t-test, and F-test, and further calibrated and validated using the coefficient of determination (R²), MSE, and RMSE. The results indicate that LARS-WG can reliably simulate future climate conditions in West Sumatra and West Kalimantan. The estimated irrigation water requirements range from 20.61 – 48.65 mm/month in West Sumatra and 22.21 – 64.47 mm/month in West Kalimantan, with the highest demand occurring in August in both regions. Regression analysis reveals that minimum temperature, maximum temperature, and precipitation have a weak influence on rice productivity, but a moderate influence on irrigation water requirements in both regions.
Reupload Repositori File 11 Februari 2026_Kholif Basri
Keywords: HUMANITIES and RELIGION::History and philosophy subjects::History subjects::Agricultural history; particularly; temperature fluctuations; rainfall patterns; and extreme